2015
DOI: 10.1186/s12912-015-0075-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of a clinical nurse consultant in an Australian Health District: a quantitative survey

Abstract: BackgroundThis study replicates previous research undertaken in 2013 that explored the role of the Clinical Nurse Consultant in a metropolitan health district in Sydney, Australia.MethodsA descriptive survey, using Likert scales, was used to collect data from Clinical Nurse Consultants.ResultsClinical Nurse Consultants are well informed about the domains and functions of their role, as stipulated in the relevant award. They identified clinical service and consultancy as the area in which they predominantly pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Globally, healthcare systems face a myriad of complex challenges, placing clinical leadership firmly in the spotlight. With nurse and therapy consultants occupying the most senior clinical role in the UK healthcare system, the role has been adopted by Australia (Wilkes, Luck, & O'Baugh, ), Hong Kong (Chan et al., ) and Italy (Portoghese et al., ), with a range of leadership roles already existing in the USA (Gantz et al., ). Nevertheless, in spite of its popularity, the role seems to be fraught with ambiguity and lack of clarity.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, healthcare systems face a myriad of complex challenges, placing clinical leadership firmly in the spotlight. With nurse and therapy consultants occupying the most senior clinical role in the UK healthcare system, the role has been adopted by Australia (Wilkes, Luck, & O'Baugh, ), Hong Kong (Chan et al., ) and Italy (Portoghese et al., ), with a range of leadership roles already existing in the USA (Gantz et al., ). Nevertheless, in spite of its popularity, the role seems to be fraught with ambiguity and lack of clarity.…”
Section: Introductionmentioning
confidence: 99%
“…For example,Drennan et al (2009) demonstrated that nurses and midwives are willing to embrace prescriptive authority as an aspect of role expansion.Although practitioners may occupy designated specialist or advanced practice roles, the extent to which they can fully express the role may be contingent on their self-perceived understanding of their scope of practice within the role. For example,Wilkes, Luck, and O'Baugh (2015) reported that fewer than half of a sample of CNC in Sydney, Australia, believed that research was part of their role and this was reflected in the fact that half of the sample did not actually conduct research. Sangster-Gormley, Martin-Misener, Downe-Wamboldt, and Dicenso (2011) identified barriers among NPs in Canada, which constrained them in their ability to practice to their full scope.…”
mentioning
confidence: 99%
“…The lower score for the ‘role of researcher’ aligns with the literature, such as the work by Wilkes et al . () who found only 43·7% of specialist nurses thought research should be a frequent part of their role. This is not to suggest these nurses are not informing their practice with best evidence, rather this was not a frequently enacted part of their role.…”
Section: Discussionmentioning
confidence: 99%
“…However, the five (5) domains they work in are as follows: clinical service and management planning, clinical services planning and consultancy, clinical leadership, research and education (Wilkes et al . ). The Australian Institute of Health and Welfare () estimates there will be 15,740 new cases of breast cancer in Australia in 2015, which equates to 12·4% of all new cases of cancer.…”
Section: Introductionmentioning
confidence: 97%